Peran koperasi perikanan KUD Mina Samudera dalam pengembangan usaha manajemen ekonomi produktif masyarakat pesisir Banten - Merissa Fermica Iskandar; Sundoro, Aries; Dirgantoro, Bagus; Afrilia Sari, Kelara; Rahayu, Dewi (Universitas Tangerang Raya, 2023)
Fisherman poverty alleviation can be done by developing Fisheries Cooperatives. For this reason, Fisheries Cooperatives were developed which aim to advance the welfare of members in particular and society in general. The research method used is a qualitative research method. In analyzing the data, the author uses descriptive analysis so that he can reveal clearly how the existence of the KUD Mina Samudera Fisheries Cooperative is in the economic development of the Muara Cituis Coastal community. In this case, the KUD Mina Samudera Fisheries Cooperative has formed several efforts to develop the economy of the Citius fishing community, there are 4 businesses including: (1) Savings and Loans Business Unit, (2) Grameen Coastal Unit, (3) SPBU-N Business Unit 39.15501 and (4) ) Coastal Shopping Business Unit. Through literature studies and interviews the author obtained research data. The proof is that the Mina Samudera Banten Fisheries KUD, Fisheries KUD, in developing the economy of the fishing community in Muara Cituis through the work program that has been implemented has indications of playing a role in advancing the welfare of its members. The existence of cooperatives in Citius Village, Tangerang Regency improves the fishermen's economy through several activities in cooperatives, including building community awareness of cooperatives, as a provider of working capital needs through savings and loan activities, and as a medium for increasing fishermen's income.